(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the percentage of death or survival of patients suffering from post-myocardial infarction ventricular septal rupture. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at the Emergency and Cardiology wards of the Idris Teaching Hospital / Sialkot Medical College Sialkot from Jan 2018 to June 2019. Materials and Methods: A total of 45 diagnosed cases with post myocardial infarction ventricular sepal defect were selected for this study. All the patients were treated according to the treatment protocols of cardiology department. The outcome (death / survival) was studied during one week stay in the hospital. Results: The mean age of the patients was 61.0±9.9 years. There were 21 (46.7%) male patients and 24 (53.3%) female patients. Eleven (24.4%) patients out of 45 were thrombolysis. In the distribution of patients by outcome, there were 21 (46.7%) patients who survived and remaining 24 (53.3%) patients died at the end one- week hospital stay. Conclusion: This study demonstrates a high percentage of mortality in patients suffering from post-myocardial infarction ventricular sepal rupture during their one-week stay in the hospital. Old age and female gender carried a substantially increased risk of mortality in cardiac rupture.